2012
DOI: 10.1111/j.1475-2743.2012.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil structural stability and erosion rates influenced by agricultural management practices in a semi‐arid Mediterranean agro‐ecosystem

Abstract: Unsuitable agricultural practices can cause loss in soil quality and erodibility to thus increase or trigger desertification under Mediterranean conditions. A field experiment was performed at the El Teularet‐Sierra de Enguera Experimental Station (eastern Spain) to assess the influence during a 5‐yr period of different agricultural practices on physical and chemical indicators of soil quality (total and water‐soluble carbohydrates, glomalin‐related soil proteins (GRSP), total organic carbon, aggregate stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 44 publications
3
93
0
3
Order By: Relevance
“…Lack of ground cover protection in windy seasons and decreasing organic carbon in soils are the main sources of risks with regard to wind erosion and desertification for croplands in the study area. The decrease of SOC may contribute to the deterioration of soil structural integrity and various functions that can lead to erosion and desertification problems, as revealed by studies conducted in North American and Mediterranean dryland areas (Li et al 2008;Maestre and Puche 2009;Garcia-Orenes et al 2012). Furthermore, decreased SOC storage capacity brought about by cropland expansion at local scales in dryland ecosystems weakens the high potential for these areas as carbon sinks, with far reaching implications for global change (Lal 2004).…”
Section: Potential Ecological Risks Concerning Soc Changementioning
confidence: 99%
“…Lack of ground cover protection in windy seasons and decreasing organic carbon in soils are the main sources of risks with regard to wind erosion and desertification for croplands in the study area. The decrease of SOC may contribute to the deterioration of soil structural integrity and various functions that can lead to erosion and desertification problems, as revealed by studies conducted in North American and Mediterranean dryland areas (Li et al 2008;Maestre and Puche 2009;Garcia-Orenes et al 2012). Furthermore, decreased SOC storage capacity brought about by cropland expansion at local scales in dryland ecosystems weakens the high potential for these areas as carbon sinks, with far reaching implications for global change (Lal 2004).…”
Section: Potential Ecological Risks Concerning Soc Changementioning
confidence: 99%
“…Different mulches have been tested to protect soil -rice straw, wood and olive residues, pine needle, and other vegetable residues (Cerdà and Doerr, 2008;García-Orenes et al, 2012;Prats et al, 2012;Jiménez et al, 2013) -and to improve the soil quality (Stavi et al, 2012). However, the review of the scientific literature published about mulch in soil conservation shows us that the use of coffee husks as mulch has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the conserved treatments did not significantly increase soil cover or affect runoff, but soil losses were low in all cases. García-Orenes et al (2012) demonstrated that the use of a cover (plants or straw) contributes to increases in soil quality and reduces the risk of erosion. Liu et al (2012) evaluated the effects of rice straw mulch and plastic film mulching at plot scale over 2 years in the Xiaofuling watershed in the Danjiangkou Reservoir area, China.…”
Section: Introductionmentioning
confidence: 99%